2009
DOI: 10.1007/s10856-009-3697-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and in vitro performance of apatite–wollastonite glass ceramic reinforced hydroxyapatite composite fabricated by 3D-printing

Abstract: In situ hydroxyapatite/apatite-wollastonite glass ceramic composite was fabricated by a three dimensional printing (3DP) technique and characterized. It was found that the as-fabricated mean green strength of the composite was 1.27 MPa which was sufficient for general handling. After varying sintering temperatures (1050-1300 degrees C) and times (1-10 h), it was found that sintering at 1300 degrees C for 3 h gave the greatest flexural modulus and strength, 34.10 GPa and 76.82 MPa respectively. This was associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(57 citation statements)
references
References 28 publications
0
57
0
Order By: Relevance
“…Received: January 16,2014 Final Version: February 27, 2014 C [284] ZrC [160] TiC/Ni [289] Al 2 O 3 -ZrO 2 [191] Polymer-derived ceramics: see present work Functional ceramics BaTiO 3 [40,41] PZT [89] PZT [211,223,239] BaTiO 3 [150] SiO 2 -Al 2 O 3 -RO-glass [269] PZT [37,[45][46][47] BaTiO 3 [115] SiCN [225] PZT [145,146] LZSA-Glass [272] TiO 2 [43,44] PMN [192] PZT [282] LSMO/YBCO [48] LiFePO 4 [170] Li 4 Ti 5 O 12 BaZrO 3 , SrTiO 3 , BaMn 2 Al 10 O 19À x [193] ITO [119] ZnO [119,187] La(Mg 0.5 , Ti 0.5 )O 3 [167,188] Zr 0.8 Sn 0.2 TiO 4 [188] TiO 2 [119] Bioceramics HA [50,66,67,[69][70][71][72] Apatite-Mullite [107][108]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Received: January 16,2014 Final Version: February 27, 2014 C [284] ZrC [160] TiC/Ni [289] Al 2 O 3 -ZrO 2 [191] Polymer-derived ceramics: see present work Functional ceramics BaTiO 3 [40,41] PZT [89] PZT [211,223,239] BaTiO 3 [150] SiO 2 -Al 2 O 3 -RO-glass [269] PZT [37,[45][46][47] BaTiO 3 [115] SiCN [225] PZT [145,146] LZSA-Glass [272] TiO 2 [43,44] PMN [192] PZT [282] LSMO/YBCO [48] LiFePO 4 [170] Li 4 Ti 5 O 12 BaZrO 3 , SrTiO 3 , BaMn 2 Al 10 O 19À x [193] ITO [119] ZnO [119,187] La(Mg 0.5 , Ti 0.5 )O 3 [167,188] Zr 0.8 Sn 0.2 TiO 4 [188] TiO 2 [119] Bioceramics HA [50,66,67,[69][70][71][72] Apatite-Mullite [107][108]…”
Section: Discussionmentioning
confidence: 99%
“…He quantified the optimal powder parameters such as the particle size (20-35 mm), compaction rate r Tapped /r Bulk (1.3-1.4), flowability ff c , defined as the ratio of consolidation stress s 1 and the compression strength s c (5-7), and powder bed surface roughness (10-25 mm). The need for at least one post-processing step (cold-isostatic pressing, [61] infiltration with preceramic polymers [62,63] or liquid metals, [51,64] chemical vapor infiltration, [65] and sintering [66,67] ) reduces the productivity of three-dimensional printing methods, so several approaches exist to increase the green density. It was observed that implementation of binder-coated particles effectively improves the green and sintered strengths.…”
Section: Three-dimensional Printing (3dp)mentioning
confidence: 99%
“…Composite materials such as combinations of ceramic (TCP), BioGlass, or polymers (natural polymers like collagen) have also been studied for use in 3DP. Composites can be formed either during printing using a polymeric binder with ceramic powder 31 or by initially starting with a ceramic / polymer powder blend 32 and an acid binder. However, powder and binder materials need to be selected with care as free radical initiators after printing can compromise biocompatibility.…”
Section: Jariwala Et Almentioning
confidence: 99%
“…2). Recently, a 3D printing technique has been developed to fabricate more ideal porous scaffolds with better control of pore morphology, pore size and porosity, with materials such as bioactive glass, hydroxyapatite, tricalcium phosphate and polymer scaffolds [61][62][63][64][65][66]. The significant advantage of this new technique for scaffold fabrication is that scaffolds with precisely controlled architectures can be printed from computer-assisted showed that Sr-MBG scaffolds exhibited a slower ion dissolution rate and more significant potential to stabilize the pH environment with increasing Sr substitution.…”
Section: Accepted Manuscriptmentioning
confidence: 99%